POTENSI PAJAK BUMI DAN BANGUNGAN SEKTOR PERDESAAN DAN PERKOTAAN KOTA YOGYAKARTA DAN KONTRIBUSINYA TERHADAP KEMANDIRIAN DAERAH - Kumoro, Merlinda Putri; Ariesanti, Alia (Universitas Muhammadiyah Surakarta, 2017)
PBB-P2 is a type of tax in Indonesia, which in 2012 was converted into local tax from state tax. The purpose of this study was to determine the potential of the PBB-P2 in Yogyakarta, as a source of real local income (PAD), and the contribution of PBB-P2 P2 to reach the level of the regions autonomy. The object of this study is the city of Yogyakarta and the method of data analysis using quantitative descriptive. The data of this research is secondary data, which is sourced from the relevant local government agencies between 2006 until 2015. The data is processed to calculate the potential PBB-P2, and its contribution to regionâs autonomy. The results of this study indicate that the target of PBB-P2 which set by the government of Yogyakarta only 24.68% of the potential, which means targeting of PBB-P2 revenue on Yogyakarta is not optimal. When compared with the realization, the revenue of the PBB-P2 only amounted to 25.56% of its potential. This result suggests that revenue of PBB-P2 has exceeded the expected targets, but still not optimal. This condition indicates that the city of Yogyakarta can increase regionâs autonomy through optimization of target setting and achievement of PBB-P2 revenue because of potential PBB-P2 which can be explored. PBB-P2 contribution rate to the PAD Yogyakarta between 2006-2015 an average of 16.15%, whereas the UN contribution to the PAD-P2 between 2006-2015 an average of 3.85%.Keywords: Potensial of PBB-P2, Yogyakarta city, regionâs autonomy